PROJETO DE VIDA - JHENIFER RIBEIRO SILVA, DAYANE; DE SOUSA OLIVEIRA, DOUGLAS; DOS SANTOS DE PAULA, LUIZ CLÁUDIO; BOTELHO VIEIRA AMORIM, MARIA CLARA; DINIZ DA SILVA , THAÍS CRISTINA; NUNES SILVA, VITÓRIA; PRADO BARBOSA, YANNE ELVIA; SILVA, CELSO RENATO (Sinapse Múltipla, 2019)